PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - ANDRES PARU NUBATONIS; JOAN YULIANA HUTAPEA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study was conducted to determine the effect of working environment on employee performances in Petrosea Offshore Supply Base - Sorong. The methodology  of this research is  quantitative research that use  questionnaire for instruments to got data. The mode of sampling techniques, we are using an non-probability mode of sampling model, and the population in this research  are the all employees on Petrosea Offshore Supply Base - Sorong, with about  68 persons. Which were taken on a certain time or period of timeline. The analysis model  used is a descriptive of statistical analysis system, coefficient of determination test, t significant test. The results of this study showed that there werw a positive and very significant effect reality  between an environment and the employee performances. Work Environment got a beta coefficient value of 0.442 which means the Work of Environment actually has a positive and also significant effect mode  on the  Employee’s  Performance within  a value of number such as  0.000